Pengaruh Penggunaan BB Cream terhadap Kejadian Acne Vulgaris pada Mahasiswa - Ari Denggan Syahputra (Program Studi Farmasi UNAJA, 2023)
Background: The use of cosmetics such as BB Cream has become increasingly common among university students, particularly females, due to its ability to provide even skin tone and a radiant appearance. However, the active ingredients and occlusive agents in BB Cream are suspected to trigger or exacerbate acne vulgaris, especially in individuals with oily or sensitive skin types. Objective: This study aimed to analyze the effect of BB Cream usage on the incidence of acne vulgaris among university students. Methods: This was an analytical observational study employing a cross-sectional design. The sample consisted of 120 female university students aged 18–24 years, selected using purposive sampling. Data were collected through structured questionnaires addressing frequency and duration of BB Cream usage, as well as dermatological clinical examinations to assess the severity of acne vulgaris. Data analysis was conducted using chi-square tests and logistic regression. Results: The findings revealed a significant association between frequent BB Cream usage (≥5 times per week) and an increased incidence of acne vulgaris (p < 0.05; OR: 2.34; 95% CI: 1.21–4.51). Moreover, usage duration longer than three months was positively correlated with acne severity. Conclusion: Frequent and prolonged use of BB Cream significantly contributes to the increased occurrence of acne vulgaris in university students. These findings highlight the need for education on appropriate cosmetic use tailored to individual skin types to prevent adverse skin health outcomes.